Ideologies in President Muhammadu Buhari's Inaugural speech - Tanko, Abubakar Musa AlKali; Ismail, Muhd Zulkifli; Abdul Jabar, Mohd Azidan; Mustapha, Nik Farhan (Medknow Publications and Media, 2022)
Ideology has a significant impact on the characteristics and behaviours of leaders. It is the vehicle through which we can comprehend our leaders, and they can understand us. This paper reveals the ideological dimensions embedded in President Muhammadu Buhari's speech, mainly his Inaugural Speech delivered in 2015. It is carried out using a Critical Discourse Analysis technique. Van Dijk's (2004) Political Ideological Strategies and Wodak's (2005) Discursive Strategies of Positive Self- and Negative Other-Presentation were incorporated to achieve the study's goal. The findings showed that Van Dijk's actor description, positive self-presentation, and negative other-presentation methods, as well as Wodak's chosen strategies of argumentation and perspectivation, were helpful in delving into the ideologies embedded in Buhari's speech. Five strategies proved to be beneficial devices in exploring the fundamentally embedded ideologies in Buhari's discourse: "Nigerian nationalism" and "nation's betrayal". Nigerian nationalism was the ideological foundation of Buhari to reform and rebuild the country. In contrast, the betrayal of the homeland and the nation was the ideological foundation of the People's Democratic Party, Boko Haram, and the Niger Delta militias. Therefore, it could be perceived that the social acts of both the in-group and the out-group were formed and structured in terms of these two ideological foundations.